IBM Spectrum LSF Suite Installation Best Practices Guide - Quintero, Dino; Black, Mark; Hussein, Ahmad; McMillan, Bill; Welch, John (IBM Redbooks, 2020)
This IBM® Redpaper publication describes IBM Spectrum® LSF® Suite best practices installation topics, application checks for workload management, and high availability configurations by using theoretical knowledge and hands-on exercises. These findings are documented by way of sample scenarios. This publication addresses topics for sellers, IT architects, IT specialists, and anyone who wants to implement and manage a high-performing workload management solution with LSF. Moreover, this guide provides documentation to transfer how-to-skills to the technical teams, and solution guidance to the sales team. This publication compliments documentation that is available at IBM Knowledge Center, and aligns with educational materials that are provided by IBM Systems.
Online resource; Title from title page (viewed March 3, 2020)
Keywords: Cloud computing; Information technology -- Management; Infonuagique; Technologie de l'information; Gestion; Information technology; Management